The prevalence of Gram-negative anaerobic bacteria in the root canal of teeth with apical periodontitis - Stanković-Nedeljković Nataša; Kocić Branislava (Serbian Medical Society - Dental Section, Belgrade, 2010)
Introduction. Bacteria from the root canal can penetrate beyond the apex and cause acute or chronic inflammation in periapical region. The aim of this study was to investigate the prevalence of different forms of apical periodontitis and to determine the presence of Gram-negative anaerobic bacteria in samples taken from the root canal and oral cavity. Materials and Methods. Study included 45 patients, 30 adults and 15 children. Three samples from the root canal and one from the oral cavity from the patients with apical periodontal inflammation were taken and grown on Schaedler agar enriched with 5% sheep blood, Schaedler agar enriched with 5% sheep blood and 20% bile, Schaedler agar enriched with 5 % sheep blood supplemented with 7.5 mg/L vancomycin and thyoglycolate broth (Biomerieux®). Final identification of bacteria was carried out by the API A system (Biomerieux®). Results. Based on clinical history and radiographic findings chronic granulomatous apical periodontitis was diagnosed in 62.2% of respondents, fibrous form in 24.4% and acute inflammation in 13.3% of cases. Porphyromonas gingivalis was isolated in 60% of the samples from the root canal and 20% of samples from oral cavity. In addition Prevotella intermedia (20%), P. melaninogenica, P. oralis, P. dentalis, Bacteroides ovatus, B. fragilis and others were also isolated. Conclusion. The most common form of the apical periodontal inflammation was chronic inflammation in the form of granuloma. Most frequently isolated bacterium was Porphyromonas gingivalis. In the samples taken from the root canal significantly more anaerobic bacteria were isolated compared to the samples from oral cavity.